Electrochemical determination of L-Tryptophan, L-Tyrosine and L-Cysteine using electrospun carbon nanofibers modified electrode - Tang, X.; Liu, Yang; Hou, H.; You, T. (Elsevier, 2010)
A novel and simple method for the direct and quantitative determination of L-tryptophan (Trp), L-tyrosine (Tyr) and L-cysteine (Cys) was proposed in this work. Carbon nanofibers (CNFs), made by electrospinning technique, were used to modify carbon paste electrode (CPE) without any treatment to study the electrochemical behaviors of the three amino acids using cyclic voltammetry (CV) and constant potential amperometric method. The results demonstrated that the CNFs modified carbon paste electrode (CNFCPE) exhibited high electrocatalytic activity and good analytical performance towards the oxidation of the three amino acids. The linear ranges of Trp, Tyr and Cys were 0.1–119, 0.2–107 and 0.15–64Mwith correlation coefficients of 0.9994, 0.9985 and 0.9996, respectively. All the detection limits of the analytes were 0.1M(S/N = 3). In addition, the CNF-CPE displayed good reproducibility, high sensitivity and good selectivity towards the determination of the amino acids, making it suitable for the determination of Trp, Tyr and Cys in clinical and medicine.